2012
DOI: 10.1007/s10535-012-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

Early gene expression in the walnut tree occurring during stimulation of leaf hydraulic conductance by irradiance

Abstract: International audienceLeaf hydraulic conductance (Kleaf) plays a significant part in plant-water regulation. In walnut leaves, Kleaf is stimulated by irradiance and closely relates to the accumulation of JrPIP2s aquaporin transcripts, but it is independent of stomatal aperture. To provide an insight into the early molecular events occurred during light-induced Kleaf, a large-scale transcriptomic analysis consisting of the cDNA-amplified fragment length polymorphism (AFLP) was carried out on walnut leaves maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…In such a context, the PIP (plasma membrane intrinsic protein) and TIP (tonoplast intrinsic proteins) subfamilies would be appropriate candidates, as their functions in water and CO 2 homeostasis are very specialised [67]. Our present results concur with studies indicating that maximal K L values and AQP transcript amounts occur at least 1 h after switching on the light [60][61][62]. Xiong et al [37] indicated that for most species the sufficient light intensity required to saturate K L is around 1000 µmol m −2 s −1 .…”
Section: Light Effects On Leaf Hydraulic Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…In such a context, the PIP (plasma membrane intrinsic protein) and TIP (tonoplast intrinsic proteins) subfamilies would be appropriate candidates, as their functions in water and CO 2 homeostasis are very specialised [67]. Our present results concur with studies indicating that maximal K L values and AQP transcript amounts occur at least 1 h after switching on the light [60][61][62]. Xiong et al [37] indicated that for most species the sufficient light intensity required to saturate K L is around 1000 µmol m −2 s −1 .…”
Section: Light Effects On Leaf Hydraulic Propertiessupporting
confidence: 89%
“…In B. pendula, a genome analysis has identified 33 putative genes encoding full-length AQP sequences [59]. The light-dependent increase of K L shows a tight correlation with AQP gene transcript abundance [60][61][62][63][64]. The activation of AQPs by phosphorylation is also associated with enhanced leaf water transport capacity [65,66].…”
Section: Light Effects On Leaf Hydraulic Propertiesmentioning
confidence: 99%
“…Three years later, 188 transcript-derived fragments (TDFs) from cDNA-AFLP in J. regia became available (Ben Bâaziz et al 2012). These were obtained as part of a study of lightinduced leaf hydraulic conductance (K leaf ), which plays a role in plant-regulation of water.…”
Section: Progress On Transcriptomicsmentioning
confidence: 99%
“…AQPs belong to a large superfamily known as major intrinsic proteins (MIPs) which selectively allow the flow of water and other small molecules through biological membranes (Baiges et al 2002). Plant AQPs play important roles in seed germination, cell elongation, stoma movement, response to stresses, and other cellular processes (Chaumont et al 1998, Jang et al 2004, Bouton et al 2005, Alleva et al 2010, Hussain et al 2011, Katsuhara et al 2011, Ben Bâaziz et al 2012, Kudoyarova et al 2013. Genome projects have revealed that more than 30 AQP genes exist in higher plants (Chaumont et al 2001, Johanson et al 2001), e.g., 35 members in Arabidopsis and at least 32 in maize.…”
Section: Introductionmentioning
confidence: 99%